2021
DOI: 10.31897/pmi.2021.2.8
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the processes of deformation and destruction of the rock sample during its extraction from great depths

Abstract: Article investigates the change in the geophysical properties of rocks in the process of extracting the rock sample from great depths. Evaluation of changes in effective elastic properties, porosity and permeability of rock samples during extraction was carried out by means of finite element modeling. Assessment of the critical dimensions and orientation of internal defects, leading to the destruction of the rock samples during extraction from great depths, has been made based on the methods of linear destruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The results of data analysis showed that the teaching materials developed were very effective for use in thematic learning. The results of the research by (Grishchenko et al, 2021) showed that the effective learning tools developed were seen from the results of the percentage of students' test completion rates of 75%.…”
Section: Discussionmentioning
confidence: 99%
“…The results of data analysis showed that the teaching materials developed were very effective for use in thematic learning. The results of the research by (Grishchenko et al, 2021) showed that the effective learning tools developed were seen from the results of the percentage of students' test completion rates of 75%.…”
Section: Discussionmentioning
confidence: 99%
“…The main growth of the explored mineral resource base reserves is provided by such fields [14,15]. A wide range of research is focused on studying the oil's properties from such fields, as well as the conditions peculiarities of their development and prospecting [12,[16][17][18][19]. Many works show the accumulation of hydrocarbons in collector rocks, which are presumably the results of biodegradation.…”
Section: Introductionmentioning
confidence: 99%